Studi Hukum: Optimalisasi Peran Jaksa Jaga Desa Dalam Mencegah Korupsi Dana Desa - Yaoma Tertibi; Arum Ayu Lestari (USRATUNA: Jurnal Hukum Keluarga Islam, 2026)
This research aims to explore the role of “Jaksa Jaga Desa” (Village Supervising Prosecutors) in the effort to prevent village fund corruption. Corruption and abuse of authority in the management of village funds are serious problems that impact community development. Through a qualitative approach, this study identifies the strategies and best practices implemented by the "Jaksa Jaga Desa" in monitoring the use of village funds. Data were collected through in-depth interviews with "Jaksa Jaga Desa," village officials, and local communities. The results of the study show that assertiveness, transparency, and community education are key factors in corruption prevention. The "Jaksa Jaga Desa" serves as both a supervisor and a mediator between the government and the community to ensure the accountability of village fund management. This research suggests improving training and inter-agency collaboration to strengthen the capacity of the "Jaksa Jaga Desa" in carrying out their duties. Thus, it is expected that the role of the "Jaksa Jaga Desa" can be optimized to create more transparent and accountable village fund management.